2014
DOI: 10.1002/adsc.201400747
|View full text |Cite
|
Sign up to set email alerts
|

External Trapping of Halomethyllithium Enabled by Flow Microreactors

Abstract: This work demonstrates that the accurate control of the reaction parameters realized within microreactor systems allowed for a taming of the reactivity of thermally unstable intermediates such as haloalkyllithiums. The first example of effective external trapping of a reactive carbenoid such as the chloromethyllithium is described. By using microreactor systems, a continuous flow synthesis of chloro alcohols and chloro amines could be achieved with high yields. By controlling the residence time the highly reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 54 publications
0
34
0
1
Order By: Relevance
“…Luisi demonstrated that (chloromethyl)lithium could be generated in the absence of the electrophile (i.e. external quenching conditions) using a flow microreactor system . (Chloromethyl)lithium was generated from 8 , with MeLi as lithiating agent, using 0.18 s as residence time, and a reaction temperature of −40 °C, sensibly higher with respect to batch conditions.…”
Section: Taming Short‐lived Organolithiums In Flowmentioning
confidence: 99%
“…Luisi demonstrated that (chloromethyl)lithium could be generated in the absence of the electrophile (i.e. external quenching conditions) using a flow microreactor system . (Chloromethyl)lithium was generated from 8 , with MeLi as lithiating agent, using 0.18 s as residence time, and a reaction temperature of −40 °C, sensibly higher with respect to batch conditions.…”
Section: Taming Short‐lived Organolithiums In Flowmentioning
confidence: 99%
“…In 2014, the first example of effective external trapping of a reactive chloromethyllithium (CML) has been reported [28]. α-Haloalkyllithiums are a useful class of organometallic reagents widely employed in synthetic chemistry.…”
Section: Reviewmentioning
confidence: 99%
“…Luisi and Degennaro reported the first example of external trapping of the highly reactive chloromethyllithium enabled by a flow microreactor system [31]. This kind of halocarbenoids, Scheme 15.…”
Section: Flow Technologymentioning
confidence: 99%